2007
DOI: 10.2320/matertrans.48.675
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of the Atomic and Electronic Structure of Nano-Hetero Metal/Inorganic Material Interfaces in Collaboration with Electron Microscopy Observations

Abstract: First-principles calculations based on density-functional theory have been applied to the energies and atomic and electronic structures of various metal/inorganic material interfaces such as metal/Al 2 O 3 , Au/TiO 2 and metal/SiC interfaces used in thermal barrier coatings, gold catalysts, and high-power electronic devices, respectively, in collaboration with electron microscopy observations. In each system, it has been shown that the interface stoichiometry, namely the features of interfacial termination spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…The distance between the Au and Ti layers at the interface is estimated from the HAADF-STEM image, which is essential to evaluate the status of oxygen layers affecting the catalytic activity. [5] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the Au and Ti layers at the interface is estimated from the HAADF-STEM image, which is essential to evaluate the status of oxygen layers affecting the catalytic activity. [5] …”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, it is quite effective to combine the structure observation by electron microscope and the first principle calculation. [4,5] For the direct observation of the atomic structure of hetero interfaces, high-resolution transmission electron microscope (HRTEM) and high-angle annular dark field scanning transmission electron microscope (HAADF-STEM) are indispensable techniques as successfully applied to various heterointerfaces. [6 -9] In the case of the interface between a nanoparticle and a metal oxide substrate, it is not so easy to determine the interface atomic structure from the combination of HRTEM and image simulations, because necessary parameters for simulations, such as the thickness of a particle and a substrate and the position of a particle in the direction parallel to the electron beam are not easily determined.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [9], we obtained that the E seg of S atom at the Al 2 O 3 (0001)/ Fe(110) interface is -0.557eV. Comparing the E seg of RE with that of S, we can conclude that Hf and Y prefer segregating in the interface than S, so the segregation of RE at the interface will suppress the segregation of S to the interface.…”
Section: Resultsmentioning
confidence: 88%
“…Atomistic modelling offers microscopic insight into inaccessible aspects of complex interface structures. For example, Kohyama et al (2007) [9] investigated the interfacial properties of Al 2 O 3 /metal, TiO 2 /Au and SiC/ metal interfaces used in thermal barrier coatings, gold catalysts, and high-power electronic devices via first principles calculations. Recently, our group examined the effects of S impurities on adhesion of Al 2 O 3 /Fe interface [10] by using DFT method, We found that the adhesion of Al 2 O 3 /Fe interface is mainly governed by Fe-O interactions between Fe and O atoms at two sides of interface, and Fe-O interactions are weakened by the segregated S impurities at Al 2 O 3 /Feinterface, so the presence of S impurities leads to a decreased adhesion for Al 2 O 3 /Fe interface.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding and controlling ceramic interfaces such as grain boundaries and ceramic/metal interfaces are crucial to develop excellent ceramics and their practical applications. First-principles calculations based on density-functional theory are effective tools to understand such interfaces in cooperation with electron microscopy observations [1]. The Schottky-barrier heights (SBH) at ceramic/metal interfaces as the discontinuity of band structures are quite important for the electronic applications, and the intrinsic mechanical properties such as tensile strength and initial failure behavior of ceramic interfaces dominate the bulk mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%